ECC Based Data Retrieval Using LoRaWAN Technology - Raad, Nibras; Mohammed Hasan, Taha; Chalak Shakir, Ahmed (International Journal of Engineering and Technology, 2018)
LoRaWAN is a low-bandwidth network technology (LPWAN) that enables low-cost and low-power communications for Internet-connected devices even in dense urban areas. This paper aimed to add an additional encryption layer plus with an electronic signature to transferred data through the Elliptic Curve Cryptography (ECC). Although this technology has important benefits such as a provides the security in data transmission where it uses the AES 128 in the process of encryption and decoding, but many studies have reported a safety vulnerability that can be exploited by brute force attack in the LoRaWAN technology termed ’Bit-flipping attack’. Accordingly, an additional layer of protection has been added to the proposed system
Keywords: Bit-Flipping Attack; LoRa/LoRaWAN; ECC; ECCDH